Pengaruh Perkembangan Teknologi dan Kualitas Sumber Daya Manusia (SDM) terhadap Fluktuasi Pengangguran di Kecamatan Pulau Punjung Kabupaten Dharmasraya - Almutia Permata Ningsih; Andis Febrian (Universitas 17 Agustus 1945 Semarang, 2025)
This research is motivated by the fact that many workplaces have followed technological developments so that many people cannot find work. This is also caused by the lack of improving the quality of human resources in Pulau Punjung District, Dharmasraya Regency so that they do not have new skills and education that does not match existing job qualifications, so unemployment fluctuations continue to rise. So researchers want to know how far the influence of technological developments and the quality of human resources is on unemployment fluctuations. The research method is Quantitative Research. Data calculated by distributing questionnaires. There were 100 respondents from this research taken from a population of 33,316 people. Data processing in this research uses SPSS 26. The results of this research show that the influence of technological developments and the quality of human resources significantly influences unemployment fluctuations. The results of this research are through the determinant coefficient test with a correlation coefficient value of 0.520 and an adjusted Rsquare value of 0.256, so the influence of X is 25.6%. The t test stated that Technological Development (X1) and Quality of Human Resources (X2) had a partial effect on Unemployment Fluctuations (y) with a calculated value of 1.968 sig value 0.000 < 0.05.